Behind the wheel: community consultation informs adaptation of safe-transport program for older drivers - Coxon, Kristy (BMC Res Notes, 2015)
BACKGROUND: Safe-transport is important to well-being in later life but balancing safety and independence for older drivers can be challenging. While self-regulation is a promising tool to promote road safety, more research is required to optimise programs. METHODS: Qualitative research was used to inform the choice and adaptation of a safe-transport education program for older drivers. Three focus groups were conducted with older drivers living in northwest Sydney to explore four key areas related to driving in later life including aged-based licensing, stopping or limiting driving, barriers to driving cessation and alternative modes of transportation. Data were analysed using content analysis. RESULTS: Four categories emerged from the data; bad press for older drivers, COMPETENCE not age, call for fairness in licensing regulations, and hanging up the keys: It’s complicated! Two key issues being (1) older drivers wanted to drive for as long as possible but (2) were not prepared for driving cessation; guided the choice and adaption of the Knowledge Enhances Your Safety (KEYS) program. This program was adapted for the Australian context and focus group findings raised the need for practical solutions, including transport alternatives, to be added. Targeted messages were developed from the data using the Precaution Adoption Process Model (PAPM), allowing the education to be tailored to the individual’s stage of behaviour change. CONCLUSION: Adapting our program based on insights gained from community consultation should ensure the program is sensitive to the needs, skills and preferences of older drivers.